Binaural summation in normals and sensorineural hearing loss - S. Venugopal and Harjeet Singh (Journal of All India Institute of Speech and Hearing, 1970)
Binaural summation was tested in fifteen normal hearing adults and fifteen subjects with bilateral symmetrical SN loss for 500 Hz & 200 Hz puretones and wideband noise of 500 m sec. duration at O dBSL, 20 dBSL & 40 dBSL. Results indicated thai SN loss group showed significantly less summation than normalsand there was a non-linear increase in summation with increasing frequency and intensity in both groups. A few theoretical explanations and recommendations are suggested.